Modernisasi Arab Saudi Era Muhammad bin Salman - Sarah, Siti; Arifin, Nana Fitriana; Ramona, Elza; Adam, Yusril Fahmi (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This research aims to examine the modernization that occurred in Saudi Arabia under the leadership of Muhammad bin Salman. The modernization of Saudi Arabia in the era of Muhammad bin Salman became important for Muhammad bin Salman's political attitude, which tended to be open to foreign cultures and move away from Wahhabism values that had been ingrained in Saudi Arabian culture. To support the analysis in the research, this article uses a historical approach and modernization theory. Through this approach and theory, this research is not only narrative-descriptive but more analytical-descriptive. The findings in this research are that the Wahhabism doctrine that developed in Saudi Arabia had a major impact not only on socio-religious aspects but also on political aspects. Through the Saudi royal authorities and Wahhabi clerics, everything that is not in accordance with the values of Wahhabism will be considered wrong and outside the pure teachings of Islam. This condition lasted until the end of King Salman's time and changed during the time of Muhammad bin Salman due to the modernity implemented in the Arab Vision 2030.Abstrak: Penelitian ini bertujuan untuk mengkaji modernisasi yang terjadi di Arab Saudi di bawah kepemimpinan Muhammad bin Salman. Modernisasi Arab Saudi di era Muhammad bin Salman menjadi penting sikap politik dari Muhammad bin Salman yang cenderung kepada keterbukaan terhadap kebudayaan luar dan keluar dari nilai-nilai Wahhabisme yang selama ini telah mengakar dalam budaya Arab Saudi. Untuk mendukung analisis dalam penelitian, artikel ini menggunakan pendekatan sejarah dan teori modernisasi. Melalui pendekatan dan teori tersebut, penelitian ini tidak hanya bersifat naratif-deskriptif, melainkan lebih kepada analitis-deskriptif. Temuan dalam penelitian ini adalah, bahwa doktrin Wahhabisme yang berkembang di Arab Saudi memberikan dampak besar tidak hanya bagi sosial-keagamaan, melainkan juga aspek politik. Melalui otoritas kerajaan Saudi dan ulama Wahhabi, segala sesuatu yang tidak sesuai dengan nilai-nilai Wahhabisme akan dianggap salah dan keluar dari ajaran Islam yang murni. Kondisi tersebut berlangsung hingga berakhirnya masa Raja Salman dan berubah pada masa Muhammad bin Salman akibat modernitas yang diimplementasikan dalam Visi Arab 2030.